Relationship investment and reciprocity: an empirical investigation. Issue 5 (1st June 2015) - Yu, Yu
Abstract : Purpose: – The purpose of this paper is to quantify the monetary amount of relationship investment in an investment banking context, investigate the drivers behind these relationship investments and look for evidence indicating reciprocity from the clients who receive these relationship investments. Relationship marketing has been one of the dominant mantras in marketing strategy circles, yet there is a lack of empirical evidence to prove significant relationship investment and reciprocity between exchange partners. Design/methodology/approach: – Relationship investment as the monetary amount by which the fair value of a loan at issuance is below its par value is measured. Regression analysis is used to study the drivers of relationship investment, including relationship depth, relationship breadth and relationship potential. Finally, reciprocity is studied as the extent to which bank's expectations are realized through future revenues. Findings: – Based on 164 loans issued by a multinational investment bank, it was found that the bank provides significant monetary benefit to its corporate clients. The amount of monetary benefit provided to each client depends on the breadth and potential of the bank-borrower relationship. The author also finds evidence suggesting that the clients reciprocated these relationship investments and the bank anticipated the reciprocity by clients. Originality/value: – This paper is the first to empirically show a significant monetary investment in a relationship-marketing context, with the intention of building stronger relationship with clients and earning future revenues through reciprocity.